Risk Factors for Arthrofibrosis in Tibial Spine Fractures: A National 10-Site Multicenter Study. Issue 7 (31st July 2020) - Aoyama, Julien; Mistovich, Justin; Yen, Yi-Meng; Ellis, Henry; Lee, Jay; Fabricant, Peter; Green, Daniel; Cruz, Aristides; McKay, Scott; Schmale, Gregory; Ganley, Theodore; Bram, Joshua
Objectives: To identify risk factors for developing arthrofibrosis after TSF treatment. Methods: This was a retrospective, multi-center study across ten institutions of 448 patients <25 years old who presented to care with a tibial spine fracture between 1/2000 and 2/2019. Patient records were reviewed for a multitude of pre-operative, intra-operative, and post-operative characteristics. Patients were then separated into two cohorts based on if they suffered from post-treatment arthrofibrosis. Results: Chart review demonstrated that 43 (9.6%) of the patients suffered from post-treatment arthrofibrosis. There were no demographic differences observed between the two groups. However, based on MRIs at the time of injury, distal femoral and proximal tibial growth plates were more frequently closed in the arthrofibrosis group (17.6% vs 4.4%, p=0.023 for both comparisons). Additionally, there was no difference in Meyers & McKeever (MM) classification (p=0.597). All arthrofibrosis patients received operative treatment (p=0.003), though there was no difference in fixation technique (p=0.734). Intraoperatively, a higher number of screws were used in the arthrofibrosis group (p=0.002) with the placement of hardware more likely to be epiphyseal (p=0.007). Other operative parameters including number of sutures were not different. Post-operatively, arthrofibrosis patients were more likely to have been immobilized in a cast (p<0.001) with no difference observed for weight-bearing status. After multivariate regression, screw number (OR 8.9, CI 1.9-41.7, p=0.005) and immobilization in a cast (OR 7.8, CI 1.0-60.4, p=0.049) remained significant predictors of post-treatment arthrofibrosis. Conclusion: This serves as the largest study of tibial spine fractures to analyze risk factors for the development of post-treatment arthrofibrosis. Our study demonstrates that pre-operative factors were largely similar between groups, but that intra-operative decisions, including the number of screws used for fixation and placement of hardware in relation to the physis, were significant predictors of post-treatment arthrofibrosis. These findings may influence operative decision-making in tibial spine fracture patients. Additionally, post-operative immobilization in a cast should be avoided given the high risk of arthrofibrosis. Table 1. Characteristics of patients with post-operative arthrofibrosis Arthrofibrosis (N=43) No Arthrofibrosis (N=405) P-value Demographic Age (years) 11.1 12.0 0.065 Male: Female ration 24:19 282:123 0.064 BMI 20.2 20.4 0.824 Injury Sports-related (%) 13 (30.2) 205 (50.4) 0.012 MM classification III/IV 20 (64.5) 134 (59.6) 0.597 Concomitant ACL injury (%) 5 (22.7) 46 (21.6) 0.902 Delay to surgery (days) 24.2 24.3 0.989 Operative Received surgery (%) 43 (100.0) 325 (78.5) 0.003 Operative time (min) 142.0 123.9 0.209 Treatment type (%) ARIF 36 (83.7) 269 (82.8) 0.734 ORIF 7 (16.3) 45 (13.8) Screws (%) 22 (51.2) 114 (35.5) 0.046 Number of Screws 1.8 1.4 0.002 Screw/Suture Placement (%) 0.005 Transphyseal 5 (17.9) 94 (44.5) 0.007 Epiphyseal 23 (82.1) 117 (55.5) Post-operative 41 (97.6) 305 (97.8) Immobilized 21 (51.2) 72 (23.7) 0.955 Cast immobilization 16 (39.0) 208 (68.2) <0.001 Non-weightbearing 11 (34.4) 72 (25.4) 0.277